Predatory Journals vs Scientific Library - Hlavcheva, Yu. N.; Olshevska, O.; Tykhonkova, I. (My University, 2023)
Science is aimed at understanding the world and discovering new technologies for the sustainable development of society and improving people's lives. The output of scientific activity can be evaluated using scientometric indicators and expert assessment. The number and interest of the scientific community in publications (citations) can indicate the quality of scientific research That is why several years ago the Ministry of Education and Sciences of Ukraine modified the requirements for publications in which the results of dissertation research must be published. However, this led to the emergence of a large number of so called «Predatory» journals and publications. Publications in predatory journals lead a loss of results, money, time, and reputation for both a researcher and his or her organization. Librarians can advise scholars on the choice of journals and the preparation of articles.
Keywords: scientific activity; predatory journals; authors; digital academic competencies; academic environment; scientific library